Application of Uplc/Ms/Ms Method for Dertermination of Sudan I in Chili Sauces - Kieu Hung, Nguyen; Quang Hien, Truong; Ngoc Hien, Tran; Thi Thuy Linh, Nguyen; Thi Ha, Nguyen (VNU Journal of Science: Earth and Environmental Sciences; Vol 39 No 3, 2023)
This study was carried out to verify and evaluate a method to quantify the relative Sudan I color product using ultra-high performance liquid chromatography coupled with tandem massspectrometry (UPLC/MS/MS). Sudan I was extracted through an Oasis HLB 3cc Vac Cartridge solid phase extraction column 60 mg, after that quantified by UPLC/MS/MS. The program uses a C18 column (2.1 x 100 mm, 1.7 µm), the mobile phase is acetonitrile and water containing 0.1% formic acid, the flow rate is 0.4 ml/min. Running conditions of MRM (Multiple Reaction Monitoring) mode, select molecular ion fragment 249 amu. The verification results have good linearity, the limit of detection (LOD) and the limit of quantification (LOQ) of the analytical procedure are 1.17 and 3.72 ng/g, respectively. The Sudan I recovery efficiency ranged from 82.00-107.33% with the relative standard deviation (RSD) between 4.35-9.04%. Highly sensitive sample extraction procedure is suitable for the determination of Sudan I in food based on 4 ionic fragments characteristics, meeting the requirements of the decision 2002/657/EC of the common European community. The verified analytical procedure was applied to quantitatively identify Sudan I in 21 chili samples. The results showed that Sudan I was not detected in all analyzed samples. The analytical procedure of Sudan I in this study could be used for food safety testing.